The Relationship of Stress Level with The Menstrual Cycle in Santriwati Pondok Krapyak Boarding School, Yogyakarta - Hodiri Adi Putra; Nur Makkiyah (Jurnal Ilmu Kesehatan Masyarakat Berkala, 2021)
Background : In adolescence, women begin with biological changes, one of which is menstruation. Every woman has a different menstrual cycle. This cycle difference is determined by several factors, one of which is stress, which is the cause of menstrual disorders. Stress is a physical or psychological reaction to demands that cause tension and disrupt the stability of everyday life. This condition results in feelings of anxiety, anger, and frustration. Purpose : to determine the relationship between stress levels and the menstrual cycle in Islamic boarding school students Krapyak Yogyakarta. Methods : This research is a type of quantitative research. The research design used a cross sectional design. The total population in this study was 320 people. The sample taken in this study using accidental sampling technique, based on this technique found a sample of 76 people. Result : It is known that most of the Santriwati Pondok Pesantren Krapyak Yogyakarta experience very heavy stress, namely 24 people (31.6%). As well as irregular menstrual cycles, as many as 49 people (64.5%). Based on the results of the calculation of the Wilcoxon signed ranks test, the Z value obtained is -6,999 with a p value (Asymp. Sig 2-tailed) of 0,000 which is less than 0.1 which means there is a relationship between stress levels and the menstrual cycle. Conclusion : Based on the results of research at the Krapyak Yogyakarta Islamic boarding school, it can be concluded that most of the santriwati experienced severe stress and most of them had irregular menstrual cycles. After a statistical test was carried out using the Wilcoxon test, it was found that there was a relationship between stress levels and the menstrual cycle among students of the Krapyak Yogyakarta Islamic boarding school.